Theoretical analysis of beam quality degradation in spectral beam combining of fiber laser array with beam deviation. (September 2018) - Bai, Gang; Shen, Hui; Yang, Yifeng; Zhao, Xiang; Zhang, Jingpu; Zhang, Haibo; Qi, Yunfeng; He, Bing; Zhou, Jun
Highlights: Study on degradation of beam quality in spectral beam combination of fiber lasers. A model with beam deviation including axial translation and angular deflection. Combined field built by coordinate transformation and beam propagation model. Statistical analysis for evaluating M 2 with random beam deviation of emitters. Accurate and applicable in fiber laser array for high power and beam quality. Abstract: Aimed to maintain excellent beam quality, the degradation of M 2 factor is theoretically studied in compact spectral beam combining (SBC) system of fiber laser array. Considering that the output beams from a laser array usually have axial translation and angular deflection, the correction of incident light field is built by the transformation of coordinates. Using the propagation model and the statistics, properties of the combined beam with perturbations of a single emitter or entire laser array are respectively discussed in detail. The degradation of M 2 factor is 0.14 ( ± 0.075 ) when the axial translation of entire laser array satisfies normal distribution with standard deviation of 100 μm. While the angular deflection is introduced with standard deviation of 10/3 mrad, the degradation increases to 3.57 ( ± 1.28 ) . Owing to non-overlap ensemble of the incident beam on the grating, the deflection angle will translate the far-field beam spot after the diffraction, which causes a dramatic degradation of the beam quality. Considering the axial translation and the angular deflection simultaneously, the overall effect on the beam quality is dominated by the angular deflection. For applicable requirements of M 2  < 2, 3 mrad angular deflection is claimed with axial translation less than 300 μm in the compact SBC system. These analyses provide a valid basis for building the experimental system of SBC.